The Suicide-Risk Factor – Data Query Tool (SURF-DQT): easy and handy access to the exhaustive base of highest evidence suicide risk factors - C.-E. Notredame; M. Ford; N. Jabari; O. Bhuiyan; S. Richard-Devantoy (Environmental Health and Preventive Medicine)
The extensive number of publications on suicide risk factors presents a practical challenge for clinicians, policy makers, and researchers to translate the research findings from academia to the improvement of individual suicide predictions and collective prevention. The Suicide Risk-Factor – Data Query Tool (SURF-DTQ) is a web application that collates organized data and helps with meta-analysis of suicidality data. Through a process of systematic review of literature according to PRISMA standards, screening and extracting studies with designs of a high level of evidence, and multi-level data synthesis, information is presented in the SURF database in a summarized, structured, and immediately relevant form. SURF allows users to search by risk factor, population, date, and indicator filters, enabling users to quickly access the most up to date and empirically grounded general or specific knowledge about suicide-related risk factors.